Pengukuran Tingkat Kesadaran Keamanan Informasi pada Mahasiswa di Lingkungan Universitas Mataram dengan Metode HAIS-Q - Shelbila, Fisabil Arum; Ariyan, Zubaidi; Raphael, Bianco Huwae; Arum, Shelbila Fisabil; Zubaidi, Ariyan; Huwae, Raphael Bianco (Universitas Bumigora, 2025)
Background: Information security is an important issue in the digital age, especially among students who actively usetechnology in both academic and non-academic activities.Objective: This study aims to determine students’ level of awareness of information security at Mataram University.Methods: The study uses the Human Aspects of Information Security Questionnaire (HAIS-Q) model, which coversthree main dimensions: knowledge, attitude, and behavior, as well as six focus areas of information security. Data wascollected through an online questionnaire distributed to active students. Analysis was conducted by calculating the averagepercentage for each dimension and domain.Result: The results indicate that the overall level of awareness among students falls into the “moderate” category. Theattitude dimension achieved the highest score at 80.01%, followed by behavior at 79.52%, and knowledge at 79.49%. TheInformation Handling and Password Management areas demonstrated strong awareness, while Internet Use had the lowestscore, particularly in the knowledge aspect.Conclusion: These findings indicate that while students have positive attitudes, their application in daily life remainssuboptimal.